A Review on Physical, Chemical and Optical Properties of Liquid Crystal - Singh, Vinod Kumar; Singh, R. K.; Dhyani, Reena; Rawat, B. S.; Rawat, P. S.; Sharma, Hemlata; Kumar, Dr. Narinder (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2023)
The foundation of the upcoming generation of cutting-edge gadgets and digitally augmented technologies is expected to be smart soft materials. Because of their responsiveness and adaptability, liquid crystals (LCs) are promising smart soft materials. In the 20th century, LCs were crucial to changing the information display sector. However, several beyond-display uses for LCs have been proven at the turn of the twentieth century, neatly using their controlled stimuli-responsive and adaptable properties. New LC materials have been developed and engineered for such applications. The review comes close with a summary and viewpoints on the potential and problems facing LCs as smart soft materials. This review is expected to inspire a wide range of concepts for the application of nature's delicate phase of matter in the generation and beyond of smart and augmented devices.